Longitudinal study of the state of training under different atmospheric pressure for best marathoners applicants in Iraq for the years (1980 – 1985) and (2005 – 2010) - Nasir, Sadoon (Journal of Physical Education, 2014)
Research included five chapters. chapter one consisted of the importance and the aims of the study and finally its field and hypotheses. Chapter two included theoretical studies which contain a brief of marathon run as well as the training in different atmospheric pressure. Chapter three tackled the procedures of the research including the method used , the subject and their training requirements and tackled about the two samples of the research Chapter four included the display of results as well as their discussion. The researcher came up with the conclusion in chapter five. Severe reduction in the amount of training in different atmospheric pressure in the annual training programs for the former and current Iraqi marathon heroes, the researcher recommended The need to take advantage of training in different air pressure and The need for attention to the principle of specialization in training the marathon, and keep up with progress in the use of catalysts to achieve the feat of digital high